High throughput mRNA sequencing reveals potential therapeutic targets of Si-Ni-San in the pons for a stress-induced depression model - Li, Junling; Zhang, Yan; Li, Te; Nie, Binbin; Qi, Fang; Chen, Qijun; Chen, Tianxing; Liu, Yuhang; Li, Gaifen; Li, Yubo (Frontiers in Pharmacology, 2024)
Background An accumulating body of research indicates that the pons is related to the occurrence of depression. Si-Ni-San (SNS) is a well-known Chinese herbal formula that is used to treat depression. Chinese herbal formulae have multiple therapeutic characteristics. Although it has been proven that SNS can exert antidepressant effects by improving changes in the limbic system, it is currently unclear whether SNS has therapeutic targets in the pons. This study aimed to explore the therapeutic targets of SNS in the pons for depression treatment. Materials and methods Two experiments were conducted. In Experiment 1, 32 rats were divided into four groups: (1) a Control (C) group that received distilled water as a vehicle; (2) a Model (M) group that received the chronic unpredictable mild stress (CUMS) procedure and was administered distilled water; (3) a Stress + SNS (MS) group that received the CUMS procedure and was administered SNS dissolved in distilled water; and (4) a Stress + Fluoxetine (MF) group that received the CUMS procedure and was administered fluoxetine dissolved in distilled water. The open field test (OFT), the sucrose preference test (SPT), and the novel object recognition test (NOR) were performed to test the antidepressant effects of SNS. High-throughput mRNA sequencing (RNA-seq) was used to explore possible gene targets of SNS in the pons, and quantitative real-time PCR was performed to verify the results. High-performance liquid chromatography was used to detect neurotransmitters. Finally, correlation analyses were conducted between behaviors, genes expression, and neurotransmitters. In Experiment 2, 18 rats were divided into the same three groups as in Experiment 1: (1) C, (2) M, and (3) MS. fMRI was used to confirm whether SNS altered the pons in a rat model of depression. Results SNS significantly improved sucrose preference in the SPT and TN-TO in the NOR compared to the M group (P < 0.05). RNA-seq filtered 49 differentially expressed genes(DEGs) that SNS could reverse in the pons of the CUMS depression model. Real-time PCR detected six genes, including Complexin2 (Cplx2), Serpinf1, Neuregulin1 (Nrg1), Annexin A1 (Anxa1), β-arrestin 1 (Arrb1) and presenilin 1 (Psen1). SNS significantly reversed changes in the expression of Anxa1, Nrg1, and Psen1 caused by CUMS (P < 0.05), which is consistent with the DEGs results. Additionally, SNS significantly reversed norepinephrine (NE) changes in the pons. There were 18 noteworthy correlations between behavior, genes, and neurotransmitters (P < 0.05). fMRI showed that SNS can decrease the amplitude of low-frequency fluctuations (ALFF) in the pons of living depressed rats. Conclusion The pons is an important target brain region for SNS to exert its antidepressant effects. SNS may improve pontine NE levels by regulating the Anxa1, Nrg1, and Psen1 genes, thereby exerting antidepressant effects and improving cognitive function.